An Overview of Probing Question Strategy in Promoting Students’ Reading Comprehension (RETAIN, 2020)
Abstract Teacher talk is considered as domination in the classroom. The role of teacher talk is a major part in managing the class so that the teaching learning process is going well. Questioning strategy in learning is a type of teacher talk that plays an important role in promoting the students’ achievements in English as Foreign Language (EFL) Classroom. The question is a stimulus that encourages students to conceive and construe a topic so that they can master the concepts, materials easily in order to support students’ reading comprehension by developing students’ high-level thinking process. In another point of view, question is a teacher’s pedagogic to construct knowledge together through stimulating students to communicate and be actively involved to ensure their comprehension. One types of questioning strategy that increasingly pointed out a great value on students’ reading comprehension is probing question. It is defined as digging question to get further answer from students who intend to develop the quality of answer, so that the answer can be clearer, more accurate and reasoned. Therefore, this paper will discussed the use of probing question and its possibilities in promoting reading comprehension. Keywords: Questioning strategy, probing question, reading comprehension